2014
DOI: 10.1007/s10555-013-9484-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fat: linking adipocyte-induced inflammation with skeletal metastases

Abstract: Adipocytes are important but underappreciated components of bone marrow microenvironment, and their numbers greatly increase with age, obesity, and associated metabolic pathologies. Age and obesity are also significant risk factors for development of metastatic prostate cancer. Adipocytes are metabolically active cells that secrete adipokines, growth factors, and inflammatory mediators; influence behavior and function of neighboring cells; and have a potential to disturb local milleu and dysregulate normal bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 218 publications
(313 reference statements)
3
119
0
Order By: Relevance
“…34,35 We hypothesized that enhanced adipocyte lineage cells in new bone sites would contribute to MM dissemination through similar mechanisms. Indeed, we found that both preadipocyte and mature adipocyte secreted factors could attract MM cells, particularly through MCP-1 and SDF-1a.…”
Section: Adipocytes Promote Myeloma Progressionmentioning
confidence: 99%
“…34,35 We hypothesized that enhanced adipocyte lineage cells in new bone sites would contribute to MM dissemination through similar mechanisms. Indeed, we found that both preadipocyte and mature adipocyte secreted factors could attract MM cells, particularly through MCP-1 and SDF-1a.…”
Section: Adipocytes Promote Myeloma Progressionmentioning
confidence: 99%
“…The number of marrow adipocytes increases greatly with aging and obesity, which are also risk factors for the development of metastatic cancers. Marrow adipocytes secrete hormones, cytokines and fatty acids that may have profound effects on hematopoietic niches, neighboring bone cells and inflammation, hence shaping the local milieu, hematopoiesis and skeletal homeostasis [147]. It has been suggested that tumor cells can also be attracted to marrow adipocytes and affected by adipokines.…”
Section: Bone Microenvironment and Macrometastasesmentioning
confidence: 99%
“…It has been suggested that tumor cells can also be attracted to marrow adipocytes and affected by adipokines. The interaction between these two cell types may create a chronic inflammatory environment that is pro-tumorigenic, as well as the translocation of adipocyte-stored lipids to the metastatic tumor cells, causing an increased motility in tumor cells [147, 148, 149]. …”
Section: Bone Microenvironment and Macrometastasesmentioning
confidence: 99%
“…Endogenous PGE 2 formation was locally increased after bone fractures, the inhibition of PGE 2 formation impairs bone healing and local administration of PGE 2 stimulated bone formation in animal studies [5]. Otherwise, the over-exposition of bones with pro-inflammatory mediators, systemic and long-term chronic inflammation causes impaired or decelerated bone healing or even Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/plefa more bone/joint destructions as known from osteo-or rheumatoid arthritis [6][7][8][9] and an imbalance of osteoblastogenesis and adipogenesis in the bone marrow cell population at the expense of osteoblast [10,11].…”
Section: Introductionmentioning
confidence: 99%